DEONTOLOGICAL ASPECTS IN THE IMPLEMENTATION OF P-Care AT THE FIRST LEVEL OF HEALTH FACILITIES IN YOGYAKARTA CITY - Zahwa Arsy Azzahra; Yayi Suryo Prabandari; Anis Fuad; Novita Indah Permatasari; Anggi Khairina Hanum Hasibuan (Jurnal Ilmu Kedokteran dan Kesehatan, 2023)
Abstract: Deontological Aspects in The Implementation of P-Care at TheFirst Level of Health Facilities in Yogyakarta City. The 2015 SustainableDevelopment Goals (SDGs) opened a new focus on Universal Health Coverage (UHC).In Indonesia, the UHC concept has been proclaimed since 2000 which is thenorganized by Badan Penyelenggara Jaminan Sosial (BPJS) following the Law of theRepublic of Indonesia number 24 of 2011 Article 9 concerning the National SecurityAdministering Body. In implementing Indonesia’s national health insurance (JKN),BPJS kesehatan uses a cloud-based information system for Fasilitas KesehatanTingkat Pertama (FKTP) / The first level health facility, namely Primary Care (P-Care)which contains medical information for more than 222 million people. According tothe Health Insurance Portability and Accountability (HIPAA), data in P-Care includesProtected Health Information (PHI) which can lead to potential ethical violations. Thisstudy aims to determine ethical issues from the Deontology aspect related to theapplication of P-Care in FKTPs in Yogyakarta City. The Method of research is thesequential exploratory mix method. The deontology point of view was chosen becausethe principle of Deontology, namely personal intrinsic value cannot be separated fromethical issues. The results showed that there are ethical issues in the application ofP-Care in FKTPs in Yogyakarta City, namely privacy and confidentiality, security, andinformed consent with the important issue being the involvement of third parties inP-Care data input, P-Care which can be accessed anywhere, lack of personalvalidation, as well as a printed diagnosis that anyone can read. The most powerfulinfluencing factor is the intrinsic value of each agent in understanding these ethicalissues.